A) (-4,-1)
B) (2,-1)
C) (2,-5)
Answer:
The answer is A) (-4,-1)
Step-by-step explanation:
You have to substitute!!! :)
A) (-4,-1):
y = 3 + x
-1 = 3 + -4
-1 = -1
YES
B) (2,-1):
y = 3 + x
-1 = 3 + 2
-1 = 5
NO
C) (2,-5):
y = 3 + x
-5 = 3 + 2
-5 = 5
NO
Answer:a
Step-by-step explanation:
If you substitue it in for a, you get 3-1=-4, which satisfies the equation.
B 6
C 3
The base is 6.
In order to find this, we can set the legs equal to each other since legs have the same length in an isosceles triangle.
x + 1 = -x + 7
2x + 1 = 7
2x = 6
x = 3
Now that we have the value for x, we can plug into the equation to get the value for the base.
3x - 3 = base
3(3) - 3 = base
9 - 3 = base
6 = base